Tinjauan Yuridis Pemenuhan Unsur Halal pada Vaksin Covid-19 dalam Upaya Melindungi Hak-Hak Masyarakat Muslim Indonesia - Andoko; Irma Fatmawati; Beby Sendy (UNISBA Press, 2022)
Abstract. The Coronavirus disease 2019 (COVID-19) pandemic has caused health, economic and social challenges globally. In these circumstances, an effective vaccine plays an important role in saving lives, improving population health, and facilitating economic recovery. In Muslim-majority countries, Islamic jurisprudence, which attaches great importance to the sanctity and safety of human life and the protection of livelihoods, may influence the uptake of vaccines. Efforts to protect humans, such as vaccines, are highly recommended in Islam. However, concerns about the Halal status (permitted for consumption by Islamic law) of vaccine products and potential hazards may hinder acceptance. The Fatwa Council agrees that vaccines are necessary in the context of our current pandemic; receiving a COVID-19 vaccination is actually a form of compliance with Sharia law. The wider use of the free animal component of the reagent during manufacture could further increase its acceptance among Muslims. Here we describe the interaction between Sharia (Islamic law) and scientific considerations in addressing the challenges of accepting the COVID-19 vaccine, particularly in Muslim populations. Abstrak. Pandemi penyakit Coronavirus 2019 (COVID-19) telah menyebabkan tantangan kesehatan, ekonomi, dan sosial secara global. Dalam keadaan ini, vaksin yang efektif memainkan peran penting dalam menyelamatkan nyawa, meningkatkan kesehatan penduduk, dan memfasilitasi pemulihan ekonomi. Di negara-negara mayoritas Muslim, yurisprudensi Islam, yang sangat mementingkan kesucian dan keselamatan hidup manusia dan perlindungan mata pencaharian, dapat mempengaruhi penyerapan vaksin. Upaya untuk melindungi manusia, seperti vaksin, sangat dianjurkan dalam Islam. Namun, kekhawatiran tentang status Halal (diizinkan untuk dikonsumsi oleh hukum Islam) produk vaksin dan potensi bahaya dapat menghambat penerimaan. Dewan Fatwa setuju bahwa vaksin diperlukan dalam konteks pandemi kita saat ini; menerima vaksinasi COVID-19 sebenarnya merupakan bentuk kepatuhan terhadap hukum Syariah. Penggunaan lebih luas dari komponen hewani gratis reagen selama pembuatan lebih lanjut dapat meningkatkan penerimaan di kalangan Muslim. Di sini kami menjelaskan interaksi antara Syariah (hukum Islam) dan pertimbangan ilmiah dalam mengatasi tantangan penerimaan vaksin COVID-19, khususnya pada populasi Muslim.